Wnt-5a induces the conversion of silent to functional synapses in the hippocampus - Álvarez-Ferradas, Carla; Wellmann, Mario; Morales, Koyam; Fuenzalida, Marco; Cerpa, Waldo; Inestrosa, Nibaldo C.; Bonansco, Christian (Frontiers in Molecular Neuroscience, 2022)
Synapse unsilencing is an essential mechanism for experience-dependent plasticity. Here, we showed that the application of the ligand Wnt-5a converts glutamatergic silent synapses into functional ones by increasing both α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) and N-methyl-D-aspartate (NMDA) currents (IAMPA and INMDA, respectively). These effects were mimicked by the hexapeptide Foxy-5 and inhibited by secreted frizzled-related protein sFRP-2. INMDA potentiation was produced by increased synaptic potency, followed by an increase in the probability of release (Pr), even in the presence of 7-nitro-2,3-dioxo-1,4-dihydroquinoxaline-6-carbonitrile (CNQX). At a longer time of Wnt-5a exposure, the Pr increments were higher in INMDA than in IAMPA. In the presence of NMDAR inhibitors, Wnt-5a-induced conversion was fully inhibited in 69.0% of silent synapses, whereas in the remaining synapses were converted into functional one. Our study findings showed that the Wnt-5a-activated pathway triggers AMPAR insertion into mammalian glutamatergic synapses, unsilencing non-functional synapses and promoting the formation of nascent synapses during the early postnatal development of the brain circuits.